R&D investment and future firm performance: The role of managerial overconfidence and government ownership - Tebourbi, Imen; Irene, Wei Kiong Ting; Le, Hanh Thi My; Qian, Long Kweh (John Wiley & Sons, Ltd., 2020)
We investigate the relationship among managerial overconfidence (MO), government ownership, and research and development (R&D) investment using data from Vietnamese public companies for the period 2007–2016. We also investigate how R&D investment, given MO and government ownership, affect future firm performance. Our results indicate that MO and government ownership are positively related to R&D investment. Conceptually, this study investigates novel factors affecting of R&D investment and their role in improving firm performance. Overall, this study emphasizes the importance of R&D investment in the corporate world, improving firm performance and, ultimately, economic prosperity.